Government Immigration Policies in Response to the COVID-19 Pandemic - Margaretha, Irene; Setiawan, Prima (KnE Social Sciences, 2022)
Novel Coronavirus Disease 2019 (Covid-19) is a virus that emerged at the end of 2019. In less than a year, the virus led to a pandemic with cross-country spread [1]. The spread of Covid-19 brought from people entering a country is referred to as an imported case [2]. In Indonesia, the first case of Covid-19 is thought to have been a close contact of foreign nationals, which implies that Covid-19 was brought from abroad and then spread locally among people in Indonesia. The Immigration Department, as part of the Government’s duties to manage the traffic of people from and to Indonesia, has an important role in handling the Covid-19 pandemic. This involves controls and restrictions on people’s movement to enter and leave Indonesian territory, and also immigration service transformation for Indonesian citizens and foreign citizens. People sometimes view immigration policies as contradictory. However, immigration policy must prioritize public health security and the national economy. This study employed the normative-empirical approach to analyzing public policy, using qualitative and descriptive methods. It was conducted to examine the Government’s strategies in the immigration sector to handle the Covid-19 pandemic and the implementation of immigration functions in the new normal era. The results showed that the Government’s strategies in the immigration sector have been dynamic, adaptive and effective. Keywords: pandemic, immigration policy, selective policy